2006
DOI: 10.1073/pnas.0507692103
|View full text |Cite
|
Sign up to set email alerts
|

In search of rat stem Leydig cells: Identification, isolation, and lineage-specific development

Abstract: Leydig cells (LCs) are thought to differentiate from spindle-shaped precursor cells that exhibit some aspects of differentiated function, including 3␤-hydroxysteroid dehydrogenase (3␤HSD) activity. The precursor cells ultimately derive from undifferentiated stem LCs (SLCs), which are postulated to be present in testes before the onset of precursor cell differentiation. We searched for cells in the neonatal rat testis with the abilities to: (i) proliferate and expand indefinitely in vitro (self renew); (ii) dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
301
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(334 citation statements)
references
References 54 publications
10
301
3
1
Order By: Relevance
“…Results showed that there was a marked but transient increase in Pdgfa and Leukemia inhibitory factor (Lif) transcript levels 24h after treatment with EDS, at a time when Leydig cell ablation was nearly complete and regeneration starting . Both LIF and PDGFA are reported to stimulate Leydig cell stem cell proliferation (Ge et al, 2006), consistent with a role in Leydig cell regeneration after EDS. Surprisingly there was a significant decrease in Dhh levels 24h after EDS treatment which recovered by 48h .…”
Section: Adult Leydig Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…Results showed that there was a marked but transient increase in Pdgfa and Leukemia inhibitory factor (Lif) transcript levels 24h after treatment with EDS, at a time when Leydig cell ablation was nearly complete and regeneration starting . Both LIF and PDGFA are reported to stimulate Leydig cell stem cell proliferation (Ge et al, 2006), consistent with a role in Leydig cell regeneration after EDS. Surprisingly there was a significant decrease in Dhh levels 24h after EDS treatment which recovered by 48h .…”
Section: Adult Leydig Cellssupporting
confidence: 54%
“…In the absence of DHH and PDGFA adult Leydig cells fail to develop but this may be related to a failure of stem cell development or proliferation (Clark et al, 2000;Gnessi et al, 2000;Park et al, 2007). It has been shown that the adult testis contains stem cells which will give rise to Leydig cells (Ge et al, 2006) but the origin of these cells and where they reside within the normal testis remains unknown. Surprisingly, the immediate progenitors of the adult Leydig cells also remain in some doubt.…”
Section: Adult Leydig Cellsmentioning
confidence: 99%
“…We further explored the role of cAMP-dependent signaling as well as PDGFα and LIF, the paracrine factors that control Leydig cell development (Gnessi et al, 2000;Ge et al, 2006), in the regulation of PFLC proliferation. We observed that PDGFα significantly (1.8-fold over control, P<0.05) stimulated the proliferation of PFLCs.…”
Section: Effect Of (Bu) 2 Camp and Paracrine Factors On Pflc Prolifermentioning
confidence: 99%
“…Leydig cells can remain undifferentiated in vitro for months and can respond to growth factors to differentiate into steroidogenic precursor cells (5). After transplantation into the testes of Leydig cell-deficient mice, these stem cells recolonize normally in the host testicular interstitium and restore the serum testosterone concentration (4).…”
mentioning
confidence: 99%
“…In contrast to theca cells, their male counterparts, Leydig cells, have been studied in detail because their putative stem cells can be isolated from mouse and rat testes by flow cytometric sorting (4,5). Leydig cells can remain undifferentiated in vitro for months and can respond to growth factors to differentiate into steroidogenic precursor cells (5).…”
mentioning
confidence: 99%